A comparative study of flow regimes and thermal performance between flat plate pulsating heat pipe and capillary tube pulsating heat pipe. (25th February 2019) - Takawale, Anand; Abraham, Satyanand; Sielaff, Axel; Mahapatra, Pallab Sinha; Pattamatta, Arvind; Stephan, Peter
Highlights: A comparative study between at plate and capillary tube PHPs is conducted. Comparison is made based on the flow regimes and corresponding thermal performances. Slug-plug flow is observed to be the dominant flow regime in both the PHPs. Amplitude of oscillations is found to be higher in CTPHP as compared to FPPHP. CTPHP performs better than FPPHP due to the presence of lateral conduction in FPPHP. Abstract: This paper reports the results of an experimental study to investigate the performance comparison between two Pulsating Heat Pipes namely, a Flat Plate Pulsating Heat Pipe (FPPHP) and a Capillary Tube Pulsating Heat Pipe (CTPHP). The comparison is made based on the flow regimes and the corresponding thermal performances at heat inputs varying from 20 W to 180 W with filling ratios of 40%, 60%, and 80%. Experiments are performed in the vertical bottom heating mode with ethanol as the working fluid. The pressure inside the PHPs and temperatures at the evaporator and condenser region are measured along with a recording of the internal flow regimes using a high-speed camera. Slug-plug flow is observed to be the dominant flow regime in both the PHPs. However, the amplitude of oscillations is found to be higher in CTPHP as compared to FPPHP. The reduction in thermal resistance of FPPHP and CTPHP due to the presence of working fluid is about 83% and 35% of the corresponding thermal resistances without any working fluid respectively. CTPHP shows better thermal performance than FPPHP due to the presence of lateral conduction arising in the latter which has a detrimental effect on the slug-plug oscillations.